Asymmetry between ecosystem health and ecological quality from an Earth observation perspective - Jiapeng Xiong; Hangnan Yu; Lan Li; Meng Yuan; Jiangtao Yu (Scientific Reports)
Abstract Ecological quality (EQ) and ecosystem health (EH) are closely related. Previous studies haven’t addressed their spatial relationships fully; therefore, whether there is spatial consistency between the two remains unclear. In this study, the EQ and EH of the Mekong River Basin (MRB), located in Southeast Asia, were determined by applying the Remote Sensing Ecological Index (RSEI) and Vigor, Organization, Resilience, and Services (VORS) models, and a spatial comparative analysis was conducted. The results showed that the EQ (RSEI_mean = 0.56) and EH (EHI_mean = 0.59) had high degrees of consistency. However, some degree of differences in the EQ and EH in certain land use types, such as grassland (RSEI_mean = 0.46; EHI_mean = 0.57) and cropland (RSEI_mean = 0.41; EHI_mean = 0.47), may have been influenced by the selection of ecosystem service types prioritized by the VORS model. In addition, there were significant differences in some areas with relatively high elevations, especially in barren land areas (RSEI_mean = 0.61; EHI_mean = 0.23), showing significant spatial asymmetry. The correlation coefficient between EQ and EH increases significantly from 0.62 to 0.72 after excluding high altitude areas. These results indicate that spatial analysis of the relationship between the EQ and EH is probably applicable to natural environments with relatively low altitudes and less human activity.